Torre David au Venezuela : récits sur fond de politiques publiques menées par le gouvernement d’un « État magique » - Yaneira Wilson (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
From Hugo Chávez to Nicolás Maduro, Venezuela has been engaged since 1999 in a set of reforms referred to as the Bolivarian Revolution”. Within this framework, we are interested in exploring the production of the Great Housing Mission Venezuela (GMVV) and the case of the invasion of the squatted Torre David in 2004 by a first group of homeless people. The main questions: how can the “magic” state with its historical dependence on oil resources aim to solve the housing problems faced by society? Boneless, abandoned, still protruding, the Torre David has gone from an icon of modernity to the writing of an “uncertain” future in which Venezuelan society is immersed. Still in 2022, the Torre symbolizes a latent crisis that persists without giving any clues about its final course.